Il principio di minimo e sue applicazioni alle equazioni funzionali lectures given at the Centro Internazionale Matematico Estivo (C.I.M.E.), held in Pisa, Italy, September 1-10, 1958 - Faedo, S. (C.I.M.E. Summer Schools, 2011)
L. Nirenberg: On ellliptic partial differential equations.- S. Agmon: The Lp approach to the Dirichlet problems.- C.B. Morrey, Jr.: Multiple integral problems in the calculus of variations and related topics.- L. Bers: Uniformizzazione e moduli.